Unraveiling the Mystery: Jejunal Stenosis Post-Stroke: A Case Report - Bhakta, Priyaben; Hanssen, Diego; Fan, David (International Journal of Clinical Research, 2024)
Background: Jejunal stenotic strictures are relatively rare but have significant clinical entities and various complex etiologies characterized by the narrowing or obstruction of the jejunum. Case Report: The patient presented with a two-month history of abdominal pain, persistent nausea, bilious vomiting, and dizziness, following a left posterior cerebral artery (PCA) stroke. Workup and various imaging studies revealed stenosis of the 3rd and 4th portion of the proximal jejunum, leading to the decision to proceed with exploratory laparotomy with bowel resection and anastomosis. The histological examination of the 15cm jejunum resection revealed significant transmural inflammation, encompassing both acute and chronic components. The presence of ulcers and prominent lymphocyte infiltration was noted, along with granulation tissue and hypertrophic muscularis propria. Conclusion: The absence of focal deficits and subsequent ischemic events, accompanied by a history of inflammatory bowel disease, suggested ischemic enteritis (IE) as the primary etiology. The patient exhibited a full recovery following the surgical intervention and reported normal gastrointestinal (GI) function. This case emphasizes the necessity for further research to gain a comprehensive understanding of the pathophysiology and optimal management approaches for jejunal stenosis. It further highlights the significance of considering IE in patients with persistent GI symptoms post-stroke.